Giant cell arteritis. Part III. New trends in its treatment (role of genetically engineered drugs) - Azamat Makhmudovich Satybaldyev (Современная ревматология)
Giant cell arteritis (GCA) is a well-known vasculitis sensitive to glucocorticoid (GC) immuno-suppression. However, during long-term treatment there may be many adverse reactions that remain a serious problem so far. Since GCA encompasses a broad spectrum of clinical subtypes, ranging from severe visual loss and neurological deficits to isolated systemic signs, its treatment must be adjusted specially to each case. The literature contains contradicting recommendations for the therapy for GCA. The paper considers different treatment options for GCA, including that with neuro-ophthalmic and neurological complications, as well as the evidence for their possible adjuvant therapies. Although there is no randomized controlled clinical trial in GCA with ocular and neurological complications, the data available in the literature suggest that these patients are recommended to be admitted for high-dose intravenous methylprednisolone, monitoring, and prevention of GC-induced complications. It is expedient to use aspirin in these cases. The evidence supporting the use of methotrexate, as well as genetically engineered agents (GEAs), infliximab, etanercept) as steroid-sparing agents is discussed. Cases of using individual GEAs (adalimumab, tocilizumab and rituximab) as an alternative to GC monotherapy are described. It is concluded that there is a need for extended clinical trials evaluating the most effective and safe GC-sparing drugs.